2021
DOI: 10.1108/jabs-02-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Understanding proximity mobile payment continuance usage in Indonesia from a habit perspective

Abstract: Purpose This study aims to propose a theoretical model to explain mobile payment (MP) continuance usage in a physical store in Indonesia from a habit perspective. In detail, continuance usage was argued to be a consequence of habitual behavior which is related to specific actions conducted automatically, repeatedly and frequently. Therefore, the theoretical model was constructed on the theory of habit establishment. Design/methodology/approach In total, 220 Indonesian respondents were used to examine the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…The result shows that social influence has no significant influence over the adoption of Fintech payment services. Studies by Ahmad et al (2021); Handarkho et al (2021); Rabaai (2021); Tohang et al (2021) also found similar results on the social influence aspect. This shows that fresh graduates are not pressured by their social environment to adopt the use of Fintech payment services.…”
Section: Discussionsupporting
confidence: 65%
“…The result shows that social influence has no significant influence over the adoption of Fintech payment services. Studies by Ahmad et al (2021); Handarkho et al (2021); Rabaai (2021); Tohang et al (2021) also found similar results on the social influence aspect. This shows that fresh graduates are not pressured by their social environment to adopt the use of Fintech payment services.…”
Section: Discussionsupporting
confidence: 65%
“…Based on Table 8 for the Malaysian context, the adoption of Fintech payments is not influenced by the surrounding environment but comes from voluntary action to adopt. [43,45] also explain that Fintech users are not concerned with their surrounding environment and may simply seem to have no interest in the opinions of their respective reference group (i.e., family, friends, colleagues) in adopting Fintech payment services. Whereas for Indonesia, the result displayed a significant negative relationship with Fintech payment services adoption (Table 8), implying that social influence discourages the use of Fintech in Indonesia.…”
Section: Discussion Of the Results Of Research On The Effect Of Utaut...mentioning
confidence: 99%
“…The findings show that Malaysian fresh graduates do not consider that their trust toward a particular product or ser-vices would influence their adoption of Fintech payment services (Table 10). According to [45], the study contends that fresh graduates experience volatility, uncertainty, complexity, and ambiguity situations when dealing with Fintech payment services. In comparison, the Indonesian data reported contrasting findings where consumer trust significantly and positively affects the adoption of Fintech payment services among fresh graduates.…”
Section: Discussion Of the Results Of Research On The Effect Of Utaut...mentioning
confidence: 99%
“…Raja & Seetharaman (1970) concluded that the cause of intention to transact is because of the ease and cost of using electronic money, which is cheaper when compared to physical cash and not only cannot be counterfeited but can also be counterfeited. Continuous use intention is the willingness of customers to use the same product or service that is done automatically, repeatedly, and frequently (Handarkho et al, 2021). The continuous use of intention is also used in telecommunications and data networks for e-commerce with safeguards for consumer privacy.…”
Section: Continuance Usage Intention and Digital Paymentmentioning
confidence: 99%